Molecular studies of CAPN-10 gene (rs2975760) and its association with Insulin Resistance in Polycystic Ovarian Syndrome of Iraqi women - Al-Murshedi, Hadbaa H.; Fadhil Jawad, Ammar; Al-Tu’ma, Fadhil J.; Hadi, Eman A.; Al-Tu’ma, Maha Mohammed Kadhim (Journal of Contemporary Medical Sciences, 2022)
Objectives: To explore an association between CAPN10, SNP-44 (rs2975760) with IR condition in women with PCOS. Methods: A study included 120 participants of which 68 women have PCOS subdivide according to their body mass index (BMI) into 45 obese (BMI≥30) and 23 non-obese (BMI<30). The remaining 52 represent the control group who were apparently healthy women with normal weight and normal menstrual cycle. Patients with PCOS were selected from the Infertility Department, Gynecology and Obstetrics Teaching Hospital, Kerbala Health Directorate / Kerbala-Iraq between Nov., 2021 and June, 2022. Diagnosis of PCOS is based on 2 of 3 findings: oligo/anovulation, hyperandrogenism, polycystic ovaries in ultrasound (Rotterdam criteria). Patients were interviewed and examined for weight, height, waist circumference, and hip circumference. Venous blood samples were collected at 9 AM after an overnight fast. IR was assessed by calculating homeostatic model assessment of insulin resistance (HOMA-IR) using the formula (fasting glucose mg/dl x fasting insulin µU/ml)/405, taking normal value <2.7. Genotypes of CAPN10, SNP-44 has been identified using Allele-specific polymerase chain reaction (AS-PCR) technique. Results: The prevalence of IR based on HOMA-IR was (80%) in obese PCOS and (48%) in non-obese PCOS women. CAPN10, SNP-44 has been reconstructed and analyzed in patients and controls. Genotypes of 45 obese PCOS subjects (TT, N=26; TC, N=12; and CC, N=7), 23 non-obese PCOS subjects (TT, N=15; TC, N=6; and CC, N=2) and control subjects (TT, N=39; TC, N=11; and CC, N=2) were identified. The genotype distribution was statistically different between obese PCOS women and controls (OR=5.25, P=0.048). The association of SNP-44 allele with IR status was detected. HOMA-IR was greater in CC (10.54 ± 1.29, 9.88 ± 1.41) than in TT (3.30 ± 1.52, P<0.001; 2.82 ± 1.45, P<0.001) and TC (3.76 ± 1.58, P<0.001; 4.10 ±1.57, P<0.05) in obese PCOS and non-obese PCOS subjects respectively. Conclusion: In obese PCOS, the C allele was associated with higher insulin secretion and HOMA-IR compared with the T allele. The increased HOMA-IR is an indicator of IR. In this scenario, the C allele might be involved in the pathophysiology of insulin resistance in PCOS.